Effects of Hand Vibration on Motor Output in Chronic Hemiparesis. (18th February 2015) - de Andrade Melo, Sibele; Iancu, Andreea; Dyer, Joseph-Omer; Forget, Robert
Abstract : Background. Muscle vibration has been shown to increase the corticospinal excitability assessed by transcranial magnetic stimulation (TMS) and to change voluntary force production in healthy subjects. Objectives. To evaluate the effect of vibration on corticospinal excitability using TMS and on maximal motor output using maximal voluntary contraction (MVC) in individuals with chronic hemiparesis. Methodology. Nineteen hemiparetic and 17 healthy control subjects participated in this study. Motor evoked potentials (MEPs) and MVC during lateral pinch grip were recorded at first dorsal interosseous muscle in a single session before, during, and after one-minute trials of 80 Hz vibration of the thenar eminence. Results. In hemiparetic subjects, vibration increased MEP amplitudes to a level comparable to that of control subjects and triggered a MEP response in 4 of 7 patients who did not have a MEP at rest. Also, vibration increased the maximal rate of force production (d F / d t max ⁡ ) in both control and hemiparetic subjects but it did not increase MVC. Conclusion. Motor response generated with a descending cortical drive in chronic hemiparetic subjects can be increased during vibration. Vibration could be used when additional input is needed to reveal motor responses and to increase rate of force generation.